The challenges of climate change : children on the front line (Innocenti insight., 2014)
Children and young people represent 30 per cent of the world's population. Not only do they represent the largest group of people currently affected by climate change, but they are also more vulnerable than adults to its harmful effects. Children and young people also constitute the generation that will be required to deal with the future impacts of climate change and that will have to deliver the very deep cuts in greenhouse gas emissions that will be essential in the coming decades. This book is an attempt to redress the balance. It brings together the knowledge and opinions of 40 contributors - scientists, development workers, and experts in health, nutrition and children's rights - in an attempt to build up a clear picture of what climate change means for the children of today and tomorrow.